Riluzole attenuates the efficacy of glutamatergic transmission by interfering with the size of the readily releasable neurotransmitter pool - Lazarevic, Vesna; Yang, Yunting; Ivanova, Daniela; Fejtová, Anna; Svenningsson, Per (Neuropharmacology, 2018)
Riluzole is a potent neuroprotective agent which primarily inhibits excitatory neurotransmission interfering with presynaptic release, uptake and postsynaptic actions of glutamate by mechanisms that are not well understood. Riluzole and related prodrugs with improved blood brain barrier penetrance, are shown to be effective for the treatment of amyotrophic lateral sclerosis, ataxias, epilepsy and mood disorders. Our study was undertaken to decipher molecular and subcellular mechanisms of riluzole's antiglutamatergic effect, particularly focusing on presynaptic active zone structure and function. Applying multifarious live cell imaging techniques and amperometric glutamate recordings, we measured the impact of riluzole on presynaptic activity, synaptic vesicle recycling and glutamate release. Our in vitro and in vivo data revealed a unique mechanism whereby riluzole reduces the efficacy of glutamatergic transmission by selectively lowering the size of the readily releasable pool. This effect was correlated with the inhibition of protein kinase C-dependent Munc18-1 phosphorylation which is known to interfere with neurotransmitter release.
EVALuna2:211605